Using the model of closed-loop economy in certain branches of the agro-industrial complex - I. V. Petrunina; N. A. Gorbunova (Пищевые системы)
From agricultural production to domestic consumption of products, the food industry produces huge amounts of waste every year, which leads to contamination of soil, water and air. Waste created upon processing agricultural raw materials and using axillary materials, such as additives, certain chemical components, fuel and so on, enhances an impact of the food chain on the environment leading to depletion of natural resources. In the last few years, production branches of economy, including the agro-industrial complex, have made attempts to maintain the balance between their impact on the environment, the use of resources, well-being of the population and economic benefits. This trend stimulates the intensive development of the theory of circular (cyclic) economy or closed-loop economy and facilitates a search for methods of its realization in the real economic system. The paper summarizes the main specific features typical of circular economy: strengthened control of supply of limited natural resources and maintenance of the stable balance of renewable resources; optimization of consumption processes by development and use of products, components and materials that correspond to the highest level of their reuse; detection and prevention of negative external effects of current production activities to increase efficiency of the economic and ecological systems. With that, despite the fact that the concept of circular economy was formulated several decades ago, its comprehensive definition is still a subject of discussions. Ambiguity of the existing definitions shows that the concept of closed-loop economy has different meaning for stakeholders. The paper examines several aspects of using elements of closed-loop economy in certain branches of the agro-industrial complex, including the meat industry. A special attention in this work is given to the introduction of modern technologies and equipment for efficient processing of waste from crop husbandry, animal husbandry and meat production to include it into the economic turnover. In addition, ecological problems arising in the course of activities of enterprises of the food and processing industries are examined and the possibilities of solving these problems by introduction of the model of circular economy have been established. Risks and barriers preventing transition of Russia to the model of circular economy have been revealed. The authors propose measures and directions of scientific research aimed at the development and introduction of elements of closed-loop economy in the meat sub-complex, including related branches of the agro-industrial complex.